Prevalence of Foot and Mouth Disease in Cattle of District Buner, Pakistan - Farman Ullah; Saeed, Kausar; Shah, Said Rahat; Jawad Ahmad, Jawad Ahmad; Ikhtiar Ullah; Syed Jafar; Ali, Jawad; Khan, Imad Ali; Siddique, Aisha (Indus Journal of Bioscience Research, 2024)
Background: Foot and Mouth disease (FMD) is infectious disease in cattle caused by a virus of the family Picornaviridae, also known as Rhino virus. The disease is characterized by large fever, appears lesions in the buccal cavity due to lesions in buccal mucosa the cattle face the difficulties in feeding. Affected animals have a high temperature, which is followed by the development of blisters chiefly in the mouth and on the feet. This disease cause loss of appetite, loss of weight, reduce milk production, miscarriage also occurs in this disease and sometime it may lead to death mostly in young ones. Objective: This study aimed to assess the Prevalence of Foot and mouth disease in district Buner. Methods: The present study was conducted on the Prevalence of Foot and Mouth disease in district Buner, Pakistan during August 2023 to August 2024. During the outbreak we were visited to the local community, DVM doctors. Livestock office of district Buner, veterinary assistance, Doctors etc. In this outbreak large number of economic loses were reported of FMD among the farmers community. Results: During the study a total of (n=3565) cases of animals (cattle) of Foot and mouth disease were reported, in which (n=439) (12.3%) death cases were reported. The total recovered cases of Foot and Mouth disease were (n=2817). During the outbreak there are around (36612) cattle were vaccinated in district Buner. The study area was divided into six different tehsils. Conclusion: The most affected tehsil during the outbreak was Mandanr. Tehsil Gadezi are highly effected in which (n=1105) cases were reported with mortality rate of (n=9.5%). The most rear effected tehsil was Gagra in which only (n=286) cases of FMD were reported with mortality rate (n=17.4%).